Toni Morrison's spiritual vision : faith, folktales, and feminism in her life and literature - Nittle, Nadra (Fortress Press, 2021)
Toni Morrison's Spiritual Vision unpacks an oft-ignored but essential element of her work--her religion--and in so doing gives readers a deeper, richer understanding of her life and her writing. As Nadra Nittle's wide-ranging, deep exploration of Morrison's oeuvre reveals, to fully understand Morrison's work, one must also understand the role of religion and spirituality in her life and literature.
Keywords: Morrison, Toni -- Criticism and interpretation.; Morrison, Toni; Religion in literature.; Religion dans la littérature.; Religion in literature; Criticism, interpretation, etc.